The performance optimization of concrete bricks using a sagu fiber - Muhammad Zakaria Umar; Abdul Fattaah Mustafa (Universitas Mercu Buana, 2023)
Sagu (sinonggi/kapurung) is a typical food of the Tolaki ethnic group. Sagu (Metroxylon sagu rottb) is an endemic plant in Southeast Sulawesi Province. So far, sagu waste in the form of fibers (sagu fiber) has not been optimally utilized. Sagu fiber waste is only left to mount; some are dumped into the river, so it is feared that it could pollute the environment. Through innovation in reducing waste in the principles of sustainable construction, sagu fiber will be used as an added material to manufacture concrete brick wall pairs. This study aimed to test the compressive strength and water absorption capacity of sagu fiber concrete bricks with variations of 0%, 50%, 60%, and 70% sagu fiber under the sand. This study uses an experimental method with stages such as preparing work tools and work materials, making test objects, and testing. Data were analyzed using mathematical formulas for the compressive strength of concrete bricks and water absorption capacity, compared with SNI 3-0349-1989 for solid concrete bricks, and analyzed comparatively. Based on the test results in this research laboratory, it is concluded that a balanced composition to get good quality is found in 70% sagu fiber and 30% sand.